Towards a systems approach for river basin management—Lessons from Australia's largest river. (17th January 2018) - Thompson, R.M.; Bond, N.; Poff, N.L.; Byron, N.
Abstract: Globally, large river systems have been extensively modified and are increasingly managed for a range of purposes including ecosystem services and ecological values. Key to managing rivers effectively are developing approaches that deal with uncertainty, are adaptive in nature, and can incorporate multiple stakeholders with dynamic feedbacks. Australia's largest river system, the Murray–Darling Basin (MDB), has been extensively developed for shipping passage, irrigation, hydroelectric development, and water supply. Water development in the MDB over the last century resulted in overallocation of water resources and large‐scale environmental degradation throughout the Basin. Under the pressure of a significant drought, there was insufficient water to supply critical human, environmental, and agricultural needs. In response, a massive programme of water reform was enacted that resulted in considerable institutional, social, and economic change. The underlying policy was required to be enacted in an absence of certainty around the scientific basis, with an adaptive management focus to incorporate new knowledge. The resulting institutional arrangements were challenged by a need to generate new governance arrangements within the constraints of existing state and national structures. The ongoing reform and management of the MDB continues to challenge all parties to achieve optimization for multiple outcomes, and to communicate that effectively. As large‐scale water reform gains pace globally, the MDB provides a window of insight into the types of systems that may emerge and the challenges in working within them. Most particularly, it illustrates the need for much more sophisticated systems thinking that runs counter to the much more linear approaches often adopted in government.